Molecular Events for Promotion of Vancomycin Resistance in Vancomycin Intermediate Staphylococcus aureus - Hu, Qiwen; Peng, Huagang; Rao, Xiancai (Frontiers in Microbiology, 2016)
Vancomycin has been used as the last resort in the clinical treatment of serious Staphylococcus aureus infections. Vancomycin-intermediate S. aureus (VISA) was discovered almost two decades ago. Aside from the vancomycin-intermediate phenotype, VISA strains from the clinic or laboratory exhibited common characteristics, such as thickened cell walls, reduced autolysis, and attenuated virulence. However, the genetic mechanisms responsible for the reduced vancomycin susceptibility in VISA are varied. The comparative genomics of vancomycin-susceptible S. aureus (VSSA)/VISA pairs showed diverse genetic mutations in VISA; only a small number of these mutations have been experimentally verified. To connect the diversified genotypes and common phenotypes in VISA, we reviewed the genetic alterations in the relative determinants, including mutation in the vraSRT, graSR, walKR, stk1/stp1, rpoB, clpP, and cmk genes. Especially, we analyzed the mechanism through which diverse mutations mediate vancomycin resistance. We propose a unified model that integrates diverse gene functions and complex biochemical processes in VISA upon the action of vancomycin.